Pembelajaran Menulis Teks Prosedur Menggunakan Model Discovery Learning pada Siswa Kelas XI SMK Negeri 2 Kediri (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
The low skill of writing procedural texts in class XI students at SMK Negeri 2 Kediri is the problem behind this research. Students who tend to be passive result in educational goals in general being less achievable. One of the important things that causes this problem to arise is the lack of interest of students to take an active role in the learning process. From the problems that arise, the author intends to provide a solution that can be applied, namely using the discovery learning learning model in learning to write procedure texts. This study uses an experimental quantitative research model. The population in this study were students of class XI SMK Negeri 2 Kediri. The sample of this study consisted of an experimental class, namely class XI Multimedia 1, and a control class, class XI Accounting 1. The stages of this research were divided into three, namely initial test, test, and final test. The author hopes that this research can be a source of reference for educators in accordance with the results obtained in the study.